Chronic pain syndrome and obesity: associations of inflammatory markers with pain characteristics - T. E. Morozova; O. V. Vorob'eva; A. A. Gertsog (Лечащий Врач)
One of the common diseases that is increasingly associated with chronic pain is obesity. The association between pain and obesity is multifactorial and includes both changes in central pain perception and the potential development of systemic inflammatory mechanisms. Our purpose was to study the clinical characteristics of chronic pain syndrome in overweight and obese patients and compare it with the level of inflammatory markers. The study included 112 patients – 37 men and 75 women aged 18 to 65 years (mean age 40 [32; 49] years) with chronic pain syndrome – musculoskeletal pain of various localization, primary headaches. Participants were divided into three groups based on body mass index. The research methods included a general clinical assessment of the characteristics of the pain syndrome – the duration and number of exacerbations in the current year, the intensity of pain using a numerical pain rating scale (NPRS), the number of descriptors, laboratory examination at the time of exacerbation – ESR, C-reactive protein, IL-6, fibrinogen. Statistical analysis was carried out using the StatTech v. 2.6.1. Patients with obesity experience longer, more intense and more frequent exacerbations of chronic pain ((p = 0.010, p = 0.004, p = 0.004), more often pain affects the limbs (p = 0.018 for localization in the upper limbs and p = 0.002 for the lower, respectively). We found the correlation of pain intensity with ESR (ρ= 0.337, p < 0.001) and fibrinogen (ρ= 0.224, p < 0.037), statistically significant differences between the level of C-reactive protein and the number of exacerbations per year (p < 0.001) were revealed. The obesity negatively affects the course of chronic pain, provoking more frequent, intense, prolonged episodes, affecting the upper and lower extremities. Due to the dependence of the level of inflammatory markers on the body mass index and the identified relationship with the intensity of pain, it can be assumed that gradual weight gain may exacerbate the course of chronic pain syndrome. The specificity of the relationship between inflammatory markers and pain severity shown in the study suggests that the relationship between obesity and chronic pain is not direct but is likely mediated by various factors.